Lung transplantation from uncontrolled and controlled donation after circulatory death: similar outcomes to brain death donors. (22nd October 2021) - Campo‐Cañaveral de la Cruz, Jose Luis; Crowley Carrasco, Silvana; Tanaka, Shin; Romero Román, Alejandra; Hoyos Mejía, Lucas; Gil Barturen, Mariana; Sánchez Calle, Álvaro; García Fadul, Christian; Aguilar Pérez, Myriam; Pérez Redondo, Marina; Naranjo Gómez, Jose Manuel; Royuela, Ana; et al.
Summary: Controlled donation after circulatory death donors (cDCD) are becoming a frequent source of lungs grafts worldwide. Conversely, lung transplantations (LTx) from uncontrolled donors (uDCD) are sporadically reported. We aimed to review our institutional experience using both uDCD and cDCD and compare to LTx from brain death donors (DBD). This is a retrospective analysis of all LTx performed between January 2013 and December 2019 in our institution. Donor and recipient characteristics were collected and univariate, multivariate and survival analyses were carried out comparing the three cohorts of donors. A total of 239 (84.7%) LTx were performed from DBD, 29 (10.3%) from cDCD and 14 (5%) from uDCD. There were no statistically significant differences in primary graft dysfunction grade 3 at 72 h, 30‐ and 90‐day mortality, need for extracorporeal membrane oxygenation after procedure, ICU and hospital length of stay, airway complications, CLAD incidence or survival at 1 and 3 years after transplant (DBD: 87.1% and 78.1%; cDCD: 89.7% and 89.7%; uDCD: 85.7% and 85.7% respectively; P  = 0.42). Short‐ and mid‐term outcomes are comparable between the three types of donors. These findings may encourage and reinforce all types of donation after circulatory death programmes as a valid and growing source of suitable organs for transplantation. Abstract : Lung transplantation from uncontrolled and controlled donors after circulatory death offers similar outcomes to brain death donors in terms of early and mid‐term results. Overall survival and CLAD‐free survival at 1 and 3 years are comparable between the three types of donors.